PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) SEMBADA MERAH DENGAN PEMBERIAN MACAM PUPUK KANDANG DAN DOSIS PUPUK NPK - Rijal, Rijaidinsyah; Zamroni; Pamungkas, Djoko Heru; Widata, Sri; Sumarwoto (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effect of the type of manure and the dosage of Phonska NPK fertilizer which was tested on red sage plants. This research was conducted at